Fabrication of the Polymersomes with Unique and Even Nonequilibrium Morphologies. Issue 2 (18th November 2020) - Dou, Jinkang; Yang, Ruiqi; Du, Kun; Li, Yanran; Huang, Xiayun; Chen, Daoyong
Abstract: Herein, efficient fabrication of polymersomes that have unique and nonequilibrium morphologies is reported. Starting from preparing big polymeric vesicles sized around 2 µm with a flexible but crosslinkable structure, a controllable morphological transformation process from the vesicles via prolate vesicles and the pearl‐chain‐like structure, which are the two intermediate structures, to vesicle‐end‐capped tubes is conducted. Significantly, each of the intermediates is a regular polymersome and occupies a distinct phase space in the transformation process and thus can be separately processed and prepared. By crosslinking the structures, respectively, regular polymersomes with unique but stable morphologies are fabricated. Furthermore, the 1D polymersomes contain narrow necks. These narrow necks are sensitive to ultrasound vibration and broken by gentle ultrasound treatment to form regular open‐ended tubes and open‐ended vesicles, which are nonequilibrium but stable morphologies and difficult to prepare by existing methods. Abstract : Highly controllable morphological transformation of poly( N, N ‐dimethylaminoethyl methacrylate)‐ block ‐poly{benzyl methacrylate‐ co ‐4‐methyl‐[7‐(methacryloyl)oxy‐ethyl‐oxy]coumarin} assemblies in water/acetone mixture solvent is applied to prepare vesicles, prolate vesicles, pear‐chain‐like structure, and vesicle‐end‐capped tubes, respectively. More significantly, the last two kinds of the assemblies can further evolve into open‐ended vesicles and open‐ended tubes, which are nonequilibrium morphologies.